Fibromyalgianess and glucocorticoid persistence among patients with rheumatoid arthritis. (22nd July 2021) - Wallace, Beth I; Moore, Meriah N; Heisler, Andrew C; Muhammad, Lutfiyya N; Song, Jing; Clauw, Daniel J; Bingham, Clifton O; Bolster, Marcy B; Marder, Wendy; Neogi, Tuhina; Wohlfahrt, Alyssa; Dunlop, Dorothy D; et al.
Abstract: Objectives: Over one-third of patients with RA exhibit evidence of fibromyalgianess, which is associated with higher rates of disability and inadequate responsiveness to RA treatment. Patients with RA often remain on glucocorticoids long-term, despite the known risk of dose-dependent morbidity. We undertook this study to examine the relationship between fibromyalgianess and glucocorticoid persistence among RA patients. Methods: We followed participants with active RA on oral prednisone for ∼3 months after initiating a new DMARD. Fibromyalgianess was measured using the Fibromyalgia Survey Questionnaire (FSQ), previously shown to correlate with key FM features often superimposed upon RA. Severity of fibromyalgianess was stratified as follows: FSQ <8 low, FSQ 8–10 moderate and FSQ >10 high/very high. The association between baseline fibromyalgianess and glucocorticoid persistence, defined as prednisone use at 3-month follow-up visit after DMARD initiation, was assessed using multiple logistic regression adjusted for baseline demographics, RA duration, serostatus and inflammatory activity assessed using swollen joint count and CRP. Results: Of the 97 participants on prednisone at baseline, 65% were still taking prednisone at follow-up. Fifty-seven percent of participants with low baseline fibromyalgianess had persistent glucocorticoid use, compared with 84% of participants with high or very high fibromyalgianess. After adjustment for non-inflammatory factors and inflammatory activity, participants with high/very high baseline fibromyalgianess were more likely to be taking prednisone at follow-up relative to those with low fibromyalgianess [odds ratio 4.99 (95% CI 1.20, 20.73)]. Conclusion: High fibromyalgianess is associated with persistent glucocorticoid use, independent of inflammatory activity.